2008
DOI: 10.1016/j.physletb.2007.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Separability of Dirac equation in higher dimensional Kerr–NUT–de Sitter spacetime

Abstract: It is shown that the Dirac equations in general higher dimensional Kerr-NUT-de Sitter spacetimes are separated into ordinary differential equations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 17 publications
(22 reference statements)
3
137
0
Order By: Relevance
“…In fact, the separability of the massive Dirac equation was already demonstrated [189]. We expect that, similar to the 4-dimensional case [32], [126], in higher dimensions also the separability of the Dirac equation can be characterized by the corresponding symmetry operators.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In fact, the separability of the massive Dirac equation was already demonstrated [189]. We expect that, similar to the 4-dimensional case [32], [126], in higher dimensions also the separability of the Dirac equation can be characterized by the corresponding symmetry operators.…”
Section: Discussionmentioning
confidence: 59%
“…We have further demonstrated that the Hamilton-Jacobi and Klein-Gordon equations allow complete separation of variables in this spacetime. The separability of the Dirac equation was proved in [189]. We have also shown that the Nambu-Goto equations for a stationary test string in the Kerr-NUT-(A)dS background can be completely separated, and that the problem of finding parallelpropagated frames in these backgrounds reduces to the set of the first order ordinary differential equations.…”
Section: Summary Of Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Specifically, when all the eigenvalues are functionally independent h was called a principal conformal Killing-Yano (PCKY) tensor [16,17,20] and the metric possesses many interesting properties. Namely, since the PCKY tensor is completely nondegenerate, one can extract from it a sufficient number of explicit and hidden symmetries [20] which ensure complete integrability of geodesic motion [25][26][27], separability of the Hamilton-Jacobi [28], KleinGordon [28,29], Dirac [30][31][32], and stationary string [33] equations, as well as separability of certain gravitational [34,35] perturbations. The metric is of the algebraic type D [36].…”
Section: Black Holesmentioning
confidence: 99%